EKSPLORASI KETERAMPILAN KERUANGAN MENGENAI KUBUS MELALUI WAWANCARA KLINIS BERBASIS MASALAH - Antonius Medellu; Sugiatno Sugiatno; Agung Hartoyo (UNIVERSITAS TANJUNGPURA, 2020)
Students’ spatial skills in solving problems related to the arrangement of cubes were relatively low. This research was conducted to describe students' spatial skills regarding cube arrangement through problem-based clinical interviews. The design of this study was descriptive exploratory using one class of students as the research sample. Student tests were used to see students' initial abilities regarding cube arrangements. While problem-based clinical interviews were used to dig deeper into spatial skills and student problem solving regarding cube arrangements. The data obtained was processed using descriptive statistics such as average, cumulative frequency and percent score. Furthermore, the data was analyzed and interpreted using qualitative data analysis techniques to explain the phenomena that occur in the field. The results of the study show that the students' spatial skills regarding the cube were still relatively low; students' spatial skills were not in accordance with the concepts related to solving the problem of unit cube arrangements; students' spatial skills did not show skills related to solving problems in unit cube arrangements; to transform students' skills into spatial skills related to the problem of cube arrangement it is necessary to re-emphasize spatial skills which include spatial visual, spatial perception, spatial relations, and spatial orientation.Keywords: Spatial Ability, Problem Based Clinical Interview